2005
DOI: 10.1542/peds.2005-0650
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Laparoscopy and Thoracoscopy in Neonates

Abstract: ABSTRACT. Objectives. Video-surgery in neonates is recent. Data on the respiratory, hemodynamic, and thermic effects during the first month of life are still sparse. This study aimed to evaluate the tolerance of videosurgery in neonates and to determine the risk factors of per-operative complications.Methods. From 1994 to 2004, 49 neonates (mean age: 11 days; weight: 3285 g) underwent 50 video-surgical procedures. Indications for laparoscopy were duodenal atresias, volvulus with malrotation, pyloric stenosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 30 publications
1
40
0
2
Order By: Relevance
“…On the basis of our preliminary work [15], we conducted a multicentric study to evaluate the safety and complication rate of laparoscopy and thoracoscopy during the first month of life based on the experience of eight pediatric surgery centers to determine the risk factors for perioperative complications, to reduce their occurrence, and to describe the recent trends in videosurgical practice.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our preliminary work [15], we conducted a multicentric study to evaluate the safety and complication rate of laparoscopy and thoracoscopy during the first month of life based on the experience of eight pediatric surgery centers to determine the risk factors for perioperative complications, to reduce their occurrence, and to describe the recent trends in videosurgical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limited data available regarding the potential deleterious effects of the CO 2 PP for this age group points toward an increased sensitivity to long-lasting laparoscopies [4,7,8,16]. In adult patients, a long-lasting CO 2 PP limited to a maximum pressure of 12 mmHg is widely used [5].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data point toward an increased sensitivity of neonates [7,8,16]. Kalfa et al [8] reported on 26 anesthetic incidents among 204 neonates (mean age, 16 days; weight, 3.4 kg) related to CO 2 insufflation.…”
mentioning
confidence: 99%
“…Однако сторонники минимально инвазивных операций всерьез дискутируют о без-опасности торакоскопии, так как использование карботоракса связано с некоторыми осложнения-ми, такими как дыхательный ацидоз, гиперкарбия, легочная гипертония [15,25], и его воздействие на новорожденного во время торакоскопии все еще остается неопределенным. Экспериментальная ра-бота G. Stratmann [26] и клиническое исследование M. Bishay [27] показали, что карботоракс ассоцииру-ется со значительным интраоперационным ацидо-зом, который может приводить к нейросенсорному поражению.…”
Section: дискуссияunclassified